2020
DOI: 10.1155/2020/3180798
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of CD99 and PAX8 in a Series of 15 Molecularly Confirmed Cases of Ewing Sarcoma

Abstract: Ewing sarcomas are an uncommon group of malignant neoplasms. A multidisciplinary approach is highly recommended to reach a correct diagnosis, considering the clinical, radiological, and histopathological aspects. Since in up to 90% of cases, the translocation t (11; 22) (q24; q12) occurs resulting in a chimeric fusion transcript EWSR1-FLI-1. The pathologist has several tools in addition to conventional techniques (hematoxylin and eosin), such as immunohistochemistry, which plays a very important role in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Reports have also shown pancreatic, gastric, duodenal, appendiceal, and rectal neuroendocrine tumors with positive staining for PAX-8 [20][21][22] as well as Ewing sarcomas. 23 PAX-8 expression has been described in breast carcinoma and is an interesting finding. One study demonstrated variable weak to strong PAX-8 staining in breast carcinomas (including mucinous, micropapillary, lobular, and ductal subtypes).…”
Section: Discussionmentioning
confidence: 86%
“…Reports have also shown pancreatic, gastric, duodenal, appendiceal, and rectal neuroendocrine tumors with positive staining for PAX-8 [20][21][22] as well as Ewing sarcomas. 23 PAX-8 expression has been described in breast carcinoma and is an interesting finding. One study demonstrated variable weak to strong PAX-8 staining in breast carcinomas (including mucinous, micropapillary, lobular, and ductal subtypes).…”
Section: Discussionmentioning
confidence: 86%
“…CD99 positivity is seen in approximately 95% of ES/PNETs. 16 NKX2.2 positivity is more specific than CD99. 17 Keratin expression is seen in 25% of cases.…”
Section: Discussionmentioning
confidence: 92%
“… 21 , 22 However, despite high sensitivity, it is a nonspecific marker owing to its expression in other tumors like anaplastic large‐cell lymphoma, lymphoblastic lymphoma, synovial sarcoma (round‐cell variant), etc. 23 Similarly, vimentin is a constituent of intermediate filament, expressed in normal mesenchymal cells and provides resistance against stress. 24 The ES stains strongly for vimentin compared to lymphoblastic lymphoma.…”
Section: Discussionmentioning
confidence: 99%